2015
DOI: 10.3906/biy-1408-40
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gene expression in SIRT3 knockout liver cells

Abstract: The sirtuin (SIRT) gene family is reported to regulate critical intracellular processes from aging to cellular metabolism and repair. SIRT3 knockout (SIRT3 -/-) mice develop receptor positive mammary tumors starting at 13 months and SIRT3 expression is decreased in human breast cancer samples as well as several other diseases. It is established that carcinogenesis results from the accumulation of multiple aberrant genetic events including the activation of oncogenes and inactivation of tumor-suppressor genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…These genes are often overexpressed in human cancers, primarily in breast tumors. In contrast, several genes that were previously reported to be downregulated in human breast cancer containing B-cell translocation gene 2 (BTG2), early growth response 1 (EGR1), and Gadd4 had decreased expression with larger than 2-folds in the SIRT3-deficient hepatocytes [66]. The list of genes with larger than 2-folds in the cancer-associated pathways and genes associated with insulinlipoprotein-cholesterol metabolism is presented in Figure 1.…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 84%
See 3 more Smart Citations
“…These genes are often overexpressed in human cancers, primarily in breast tumors. In contrast, several genes that were previously reported to be downregulated in human breast cancer containing B-cell translocation gene 2 (BTG2), early growth response 1 (EGR1), and Gadd4 had decreased expression with larger than 2-folds in the SIRT3-deficient hepatocytes [66]. The list of genes with larger than 2-folds in the cancer-associated pathways and genes associated with insulinlipoprotein-cholesterol metabolism is presented in Figure 1.…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 84%
“…We have previously shown that the loss of expression of SIRT3 in mouse liver and cultured mouse embryonic fibroblasts results in a cellular environment susceptible to carcinogenesis and cellular transformation [38,66]. In the subsequent study, we investigated how SIRT3 alters the gene expression of cancer-related pathways in SIRT3 wild-type and SIRT3 knockout mouse hepatocytes.…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Seven SIRTs are found in different compartments within the cells. SIRT3, 4 and 5 are located in the mitochondria, SIRT1, 6 and 7 are mainly located in the nuclei, and SIRT2 is primarily located in the cytoplasm but it can translocate into the nucleus during cell cycle 12 . SIRTs have been reported to be involved in aging, longevity, stress response, regulation of metabolism, gene silencing, and DNA repair.…”
Section: Introductionmentioning
confidence: 99%